Analysis of Factors Related to The Mental Status of Elderly - Devita, Yeni; Nita, Yureya; Dwiguna, Stephanie; Puswati, Desti; Saputra, Rahmat; Alfianur, Alfianur (Universitas Prima Indonesia, 2024)
Mental health problems can have a significant impact on elderly. Some things related to mental disorders, such as depression and dementia in elderly, are caused by several factors, including elderly independence, family support, work, health or diseases suffered by elderly, and environment. This study aimed to determine the aspects related to the mental status of older people. This type of research is quantitative research. The population in this study is all elderly who are in the working area of UPT Puskesmas Bangko Jaya. The sampling technique uses probability sampling with a simple random sampling approach with 96 elderly samples. The analysis used is a bivariate analysis using the Chi-Square statistical test. The results showed that there was a correlation between the independence of elderly and the mental status of elderly (p-value = 0.026 < α = 0.05), There was a correlation between family support and the mental status of elderly (p-value = 0.014 < α = 0.05), There was a correlation between the history of illness and the mental status of elderly (p-value = 0.000 < α = 0.05) and There was a correlation between the elderly environment and the mental status of elderly (p-value = 0.037 < α = 0.05). The nursing profession was expected to provide advocacy and assistance to health workers in primary care, especially nursing, to improve the mental status of elderly.